2006
DOI: 10.1213/01.ane.0000184812.94185.b3
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of Thoracic Epidural Neostigmine Infusion After Thoracotomy

Abstract: Few anesthesia studies have explored perioperative continuous epidural infusion of neostigmine. We examined such a regimen in thoracotomy patients. Ninety patients were randomized to one of three groups in this double-blind trial. Before anesthesia induction, an epidural catheter was inserted in all patients at T5-8 levels under local anesthesia. Pre-neo patients received bolus 500-microg epidural neostigmine before anesthesia induction followed by infusion of 125 microg/h until the end of surgery. Post-neo pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 32 publications
0
16
0
2
Order By: Relevance
“…8,9,16,17,21 According to these previous studies, 8,9,16,17,21 no apparent dose-effect relation existed between the dose of neostigmine for epidural administration and the incidence of these adverse effects. In addition, the incidence of nausea and vomiting was not significantly higher in patients given neostigmine epidurally, compared with the incidence in those that did not receive the anticholinesterase agent.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…8,9,16,17,21 According to these previous studies, 8,9,16,17,21 no apparent dose-effect relation existed between the dose of neostigmine for epidural administration and the incidence of these adverse effects. In addition, the incidence of nausea and vomiting was not significantly higher in patients given neostigmine epidurally, compared with the incidence in those that did not receive the anticholinesterase agent.…”
Section: Discussionmentioning
confidence: 98%
“…5 This drug was found to be devoid of neurotoxic effects when injected intrathecally in dogs, rats, and sheep. 6,7 Clinical studies 8,9 in humans who underwent surgeries expected to result in severe postoperative pain demonstrated that the combination of morphine with neostigmine improved postoperative analgesia, compared with the analgesic outcome for each drug alone, without increasing adverse effects.…”
Section: Cmpsmentioning
confidence: 99%
“…Neostigmine is an acetylcholinesterase inhibitor used as a neuroaxial adjuvant drug to enhance the analgesic effect of local anesthetics. 18,19 Although neostigmine accomplishes analgesia by inhibiting endogen neurotransmitter acetylcholine degradation, increased acetylcholine in the medulla spinalis stimulates all muscarinic and nicotinic receptors. Therefore, increased acetylcholine together with analgesia leads to many adverse effects, such as motor weakness, hypertension, tachycardia, vaginal contraction, ejaculation, urinary retention, and bowel incontinence.…”
Section: Discussionmentioning
confidence: 99%
“…However, the authors assumed the lack of adverse effects nausea, vomiting, sedation, tachycardia, hypertension to the small simple size studied [112].…”
Section: Neostigminementioning
confidence: 99%